TRANSPORTING TURKISH EXAM TAKERS: A NEW USE FOR AN OLD MODEL - (:unkn) unknown (NOVA SCIENCE PUBLISHERS, INC, 2010)
This paper argues that the transportation model of linear programming can be used to administer the Public Personnel Language Exam of Turkey in many different locations instead of just one, as is the current practice. It shows the resulting system to be much less costly. Furthermore, once the decision about number of locations is made, the resulting system can be managed either in a centralized or decentralized manner. A mixed mode of management is outlined, some historical perspectives on the genesis of the transportation model are offered and some ideas regarding the reasons for the current wasteful practices are presented. The possibility of applying the same policy reform in other MENA (Middle East and North Africa) countries is discussed in brief.